The Image of Veil in Leila Ahmed’s Women and Gender in Islam - AYDIN, Asım (Journal of History Culture and Art Research, 2026)
Abstract Most of the time suppressed and disempowered throughout man’s history, the gender of woman has undergone a dissipating process where such an overpowering oscillation between two genders occurs. In spite of the fact that this bias creates a generalization, the position of the ’womanhood’ wasn’t always under subjugation. As a matter of fact, this essay intends to throw light upon women’s past, present and future’ by relying on mainly Leila Ahmed’s flagship works into by drawing a map showing how the veil plays a critical role in the representation of women.